Risk factors for obesity and overweight in under-five children in a highland community, Kabanjahe - Sibagariang, Eva Ellya; Ginting, Rapael; Sihombing, Rachel Raselia; Amir, Dwi Fenny; Meliala, Juli Elisabet Mayen Br; Angkasa, Celvin; Zubaidah, Siti; Sherliana, Ferra; Siregar, Hesti Despita (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Overnutrition in toddlers is a public health problem that continues to increase globally and nationally. In Indonesia, the prevalence of toddler obesity has risen from 10.5% (2007) to 21.8% (2018). In Karo Regency, the prevalence of toddler obesity reached 8.80%. Data from 2025 at Simpang Empat Community Health Center in Kabanjahe shows 12 toddlers with obesity and 49 toddlers with overnutrition. This study aims to analyze the relationship between maternal knowledge, attitudes, and practices with the occurrence of obesity and overnutrition in toddlers aged 12-60 months. The research method used an observational analytic design with a cross-sectional approach. The sample consisted of 61 toddlers with obesity or overnutrition, selected using total sampling. Data were collected through questionnaires and anthropometric measurements of BMI-for-age. Analysis used the Chi-Square test. Results show the majority of mothers had insufficient knowledge (57.4%), positive attitudes (63.9%), and suboptimal practices (65.6%). There was a significant relationship between knowledge (p=0.038), attitude (p=0.041), and practice (p=0.044) with the toddler's nutritional status. The study conclusion confirms that good nutritional care practices, supported by adequate knowledge and a positive attitude, play an important role in preventing obesity and overnutrition in toddlers.